2021
DOI: 10.1109/access.2021.3086839
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Generative Adversarial Network Using Spatial and Channel-Wise Attention for CS-MRI Reconstruction

Abstract: Compressed sensing (CS) can speed up the magnetic resonance imaging (MRI) process and reconstruct high-quality images from under-sampled k-space data. However, traditional CS-MRI suffers from slow iterations and artifacts caused by noise when the acceleration factor is high. Currently, deep learning has been introduced to address these issues. Although some improvements have been achieved, the reconstruction problem under high under-sampling rates has not been solved. Thus, our study proposed a novel CS-MRI re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…To further demonstrate the role of RG-CAM, the variant, dubbed "w/o RG", adopts a single kernel to perform channel-wise attention without using the spatial guiding masks, similar to [27,17,13]. From Table 2, we found that the incorporation of the region-guided mechanism enhances the model performance, comparing "w/o RG" and "proposed".…”
Section: Ablation Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…To further demonstrate the role of RG-CAM, the variant, dubbed "w/o RG", adopts a single kernel to perform channel-wise attention without using the spatial guiding masks, similar to [27,17,13]. From Table 2, we found that the incorporation of the region-guided mechanism enhances the model performance, comparing "w/o RG" and "proposed".…”
Section: Ablation Analysismentioning
confidence: 98%
“…Owing to its flexible design, RG-CAM can be easily combined with other network structures, e.g. the spatial attention modules [33,27,17], to retrieve further improvements.…”
Section: Region-guided Channel-wise Attention Module (Rg-cam)mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional CS-MRI is affected by slow iterations and noise-induced artifacts during the high acceleration factor. The RSCA-GAN uses spatial and channel-wise attention with long skip connections to improve the quality at each stage, accelerating the reconstruction process and removing the artifacts brought by fast-paced under-sampling [118]. Parallel imaging integrated with the GAN model (PI-GAN) and transfer learning accelerates MRI imaging with under-sampling in the kspace.…”
Section: A Mri Accelerationmentioning
confidence: 99%
“…Yuan et al [ 46 ] incorporated the self-attention mechanism into the generator for a global understanding of images and improved the discriminator for the utilisation of prior knowledge. Li et al [ 47 ] proposed RSCA-GAN for fast MRI reconstruction, where both spatial and channel-wise attention mechanisms were applied in the generator. This team also applied the GAN-based model with attention mechanisms in the super-resolution task [ 48 ].…”
Section: Introductionmentioning
confidence: 99%